Confusion, difficulty concentrating, and slow response induced by ropinirole therapy in an elderly patient with secondary Parkinsonism: a case report - Emilia Sidharta; Ivon Sindu Wijaya; Hanny Cahyadi (Universitas Islam Indonesia, 2020)
Abstract Background: Ropinirole is a therapy that is widely used in patients with Parkinson's disease or Restless Leg Syndrome (RLS). Some research journals show that the long-term use of ropinirole can cause side effects. But unfortunately, there are no published studies from Indonesia that show the side effects of ropinirole..Objective: To report a case of several side effects induced by ropinirole therapyMethod : Assessment methods used were time series data collection followed by causality analysis using Naranjo Scale. Results: This case reports several side effects such as confusion, difficulty concentrating, and slow response experienced by a 75-year-old elderly patient who consumed ropinirole 2 mg as a therapy for Secondary Parkinsonism. Before using ropinirole, the patient had used levodopa-benserazide, trihexyphenidyl, and pramipexole to overcome Parkinson's for more than 3 years. During the period no side effects occurred. Side effects occurred after ropinirole therapy was given to patients. The analysis using Naranjo Scale shows a score of 6 which means Probable. Conclusion: The aim of this study is to raise awareness for health workers, especially pharmacists in order to increase alertness in patients using long-term medications such as those with Parkinson's.Keywords: side effect, secondary parkinsonism, ropinirole, elderly